A high performance data integrity assurance based on the determinant technique - Ghaeb, J. A.; Smadi, M. A.; Chebil, Jalel (Elsevier BV, 2011)
Data integrity is an important aspect of storage and network security. The reality is that no security strategy is achieved without assuring data integrity. Data assurance provides reliability which is a prerequisite for most computer systems and network applications. This paper proposes a new technique for improving the detection of data integrity violations. The proposed technique is based on the Check Determinant Factor (CDF) in measuring data integrity assurance. It involves appending of a Determinant Factor (DF) for each data matrix before storing or transmitting the series of data. This DF is recomputed at the retrieved stage to ensure data integrity. Simulation results show that the new method outperforms the traditional methods such as Hamming code and RAID methods.